The Basis of Social Protests in Georgia in 2019 - Mijalska, Faustyna; Kardaś, Jarosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
Coming to power in 2012, the Georgian Dream promised changes expected by Georgian society that was torn between striving for peace and prosperity, following the example of Western countries, and stabilizing relations with Russia. After seven years, this promise was not fulfilled, and the citizens were bitter about the internal and international policies of Bidzina Ivanishvili. For the purpose of this article, the research hypothesis was formulated that in June 2019 social protests broke out in the capital of Georgia, because the activities of the party headed by Bidzina Ivanishvili resulted in decreased social confidence in this formation. The authors of the article analyzed the activities of Bidzina Ivanishvili which might have sparked social unrest and identified the internal and external factors that resulted in the shrinking social confidence in Georgian authorities in recent years. The authors presented also the events of June 20, 2019, when thousands of people gathered in front of the Georgian parliament building to express their discontent with the presence of the deputy of Russian Duma, Sergei Gavrilov, at the parliamentary session, which resulted in nationwide protests.

Gruzińskie Marzenie dochodząc do władzy w 2012 r. było obietnicą zmian, których oczekiwało społeczeństwo gruzińskie, rozdarte pomiędzy dążeniami do pokoju i dobrobytu wzorem państw zachodnich, a zarazem ustabilizowania stosunków z Rosją. Po siedmiu latach okazało się, że ta obietnica nie spełniła się, a obywatele są rozgoryczeni prowadzeniem polityki zarówno wewnętrznej, jak i międzynarodowej przez Bidzinę Iwaniszwilego. Na potrzeby artykułu sformułowano hipotezę badawczą zakładającą, że w czerwcu 2019 r. doszło do protestów społecznych w stolicy Gruzji, ponieważ działania podejmowane przez ugrupowanie kierowane przez Bidzinę Iwaniszwilego doprowadziły do spadku zaufania do tej formacji. Autorzy artykułu podjęli się próby analizy działań podejmowanych Bidzinę Iwaniszwilego, które mogły doprowadzić do niepokojów społecznych oraz wskazania czynników wewnętrznych i zewnętrznych, które doprowadziły do spadku zaufania do rządzących Gruzją w ostatnich latach. Ponadto przedstawili wydarzenia z dnia 20 czerwca 2019 r., kiedy to wielotysięczny tłum zgromadził się pod budynkiem gruzińskiego parlamentu, by wyrazić niezadowolenie z pojawienia się na sesji parlamentu deputowanego rosyjskiej dumy, Siergieja Gawriłowa, co w rezultacie wywołało ogólnopaństwowe protesty.
Podłoże protestów społecznych w Gruzji w 2019 roku
Keywords: Georgia; social protests; Russia; new social movements; conflict; Gruzja; protesty społeczne; Rosja; nowe ruchy społeczne; konflikt